History of formation and development of Think-Tanks in the world - Hanh, Nguyen Thi Minh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
Think-Tank as policy study and consultacy organization is the term used multiply by policy consultants and policy makers recently. However, there are contreversions in views to the history of formation, specific features and nature of activities of this types of policy study and consultancy organizations. The paper provides basic information on the history of formation, specific features and nature of activities as well as organizational-operational models of Thinks-Tanks in USA and China as the two leading countries in number of Think-Tanks.